Melancholy and the critique of modernity : Søren Kierkegaard's religious psychology - Ferguson, Harvie (Routledge, 1995)
The connections between the emergence of modern society and the experience of melancholy are explored through a comprehensive re-examination of Soren Kierkegaard's rich and insightful writings.